Benchmarking quantum cloud processes - Loke, Kum Yin (Nanyang Technological University, 2021)
Quantum cloud processes are quantum computers hosted on the cloud as a platform for users to test their quantum algorithms. This opens up access to quantum computers. However, quantum computers are prone to errors, so users need a method for benchmarking these cloud services. This report implements benchmarking on single qubit gates using the robustness of quantum channel as the metric. It also evaluates the usefulness of this metric as a tool for benchmarking quantum computers as well as quantum cloud processes.